MUSLIMS IN THE PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS THROUGH THE PRISM OF FREEDOM OF RELIGION IN EDUCATION (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
In this paper, the authors presented the characteristic cases from the case law of theEuropean Court of Human Rights in which members of the Islamic community consideredthat their freedom of religion under Article 9 of the European Convention on Human Rightsand Fundamental Freedoms has been violated. At the same time, in those cases, there wasfrequently violation of Article 2 of Protocol No. 1 to the Convention, which provides for theright to education, cumulatively with above mention article. The starting point is the case ofDahlab v. Switzerland, after which the authors specifically addressed several other cases inwhich the European Court of Human Rights considered these rights.
Keywords: Muslims, European Court of Human Rights, Convention, freedom of religion, right to education